1999
DOI: 10.1063/1.124039
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic detection of photogenerated currents in semiconductor wafers using superconducting quantum interference devices

Abstract: A completely noninvasive method is presented for the investigation of semiconductor wafers with high spatial resolution utilizing a superconducting quantum interference device (SQUID) magnetometer system. The method is based on the detection of the magnetic field caused by photocurrents generated in the semiconductor sample using a sensitive SQUID magnetometer. The photocurrents arise when laser light with a photon energy exceeding the band gap of the semiconductor is focused onto the sample surface in a regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Among magnetometers, superconducting quantum interference devices (SQUIDs) allow one to detect magnetic fields in the range of fT-mT. [1][2][3][4] SQUID systems, however, require very low temperatures like liquid-nitrogen or liquid-helium temperature, and their spatial resolution is limited to approximately 10 mm. 4) On the other hand, the current detection method using magnetic force microscopy (MFM) was proposed and demonstrated to obtain spatially resolved magnetic field images with topography.…”
Section: Introductionmentioning
confidence: 99%
“…Among magnetometers, superconducting quantum interference devices (SQUIDs) allow one to detect magnetic fields in the range of fT-mT. [1][2][3][4] SQUID systems, however, require very low temperatures like liquid-nitrogen or liquid-helium temperature, and their spatial resolution is limited to approximately 10 mm. 4) On the other hand, the current detection method using magnetic force microscopy (MFM) was proposed and demonstrated to obtain spatially resolved magnetic field images with topography.…”
Section: Introductionmentioning
confidence: 99%
“…A demonstration of imaging the p-n junctions in a 256 Mbit dynamic random access memory (DRAM) chip using a laser-SQUID showed that the spatial resolution was 0.59 mm in an intensity image, and 0.54 mm in a phase image. 44) This is much better than the resolution obtained using either a similar type of microscopy in the past 45,46) or conventional SQUID microscopy [47][48][49][50] (Fig. 12).…”
Section: Scanning Laser-squid For Ic Testingmentioning
confidence: 82%
“…[ 7 ] In the following years, several publications with applications in the field of photovoltaics were published. [ 8,9 ]…”
Section: Methodsmentioning
confidence: 99%